CORRELATION BETWEEN SERUM VITAMIN D LEVELS AND SEVERITY OF SCHIZOPHRENIA PATIENTS IN THE DR. SOETOMO HOSPITAL - Adil Dinata Simangunsong; Aryati Aryati; Azimatul Karimah; Ferdy Royland Marpaung (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Introduction. Vitamin D deficiency is a common health problem that occurs in various countries. Vitamin D deficiency is linked to various diseases such as kidney failure, liver damage, atherosclerosis, obesity and psychiatric disorders such as depression and schizophrenia. This study aimed to analyze the correlation between serum vitamin D levels and schizophrenia severity. Methods. Schizophrenia patients who visited the Inpatient and Outpatient Clinic Department of Psychiatry of the Dr. Soetomo Hospital Surabaya. This was a cross-sectional observational study, conducted in December 2017 - April 2018 . The subjects consisted of 53 schizophrenia patients, vitamin D levels < 30 ng /mL (35 (66.04%); > 30 ng/mL (18 (33.96%). Serum vitamin D levels test by enzyme linked fluorescent assay (ELFA) method using Vidas. The severity of schizophrenia was measured using a positive and negative syndrome scale (PANSS) score. Results. Mean serum vitamin D levels in schizophrenia were 23.45 ± 9.16 ng / mL, serum vitamin D levels in males were 24.36 ± 9.80 ng / ml and females 21.96 ± 7.98 ng / ml. The mean serum vitamin D level and PANSS scores of positive symptoms was 16.42 ± 8.50. The mean serum vitamin D level and PANSS scores of negative symptoms was 15.60 ± 6.12. The mean serum vitamin D level and PANSS scores of general psychopathology symptoms was 29.51 ± 10.29. The statistical results showed no association between vitamin D levels and PANSS scores. Conclusion. The results of this study indicated low serum vitamin D levels in schizophrenia. There was no association between serum vitamin D levels and the severity of schizophrenia using PANSS scores.